“The Development of foodPedia: An Android-based Application for Food Trails in Perak” - Fathi Nadirah bt Jamlus, Fathi Nadirah (Universiti Teknologi PETRONAS, 2012)
This study examines the extent of adoption of information communication technology (ICT) in promoting local delicacies owned by SMEs in Food and Beverages in Malaysia. It focuses on an alternative way that can be used to help these SMEs to promote their business using android, the bestselling platform which operates on smartphones and computer tablets. This paper combines and describes how people and technology complement each other for betterment of the industry. Since SMEs cover major portions of the businesses in Malaysia, it makes them one of the major contributing factors which lead towards the economic growth. Android on the other hand is chosen by looking at the positive growth of smartphones market shares and this paper shall explain how does this relates to android to be chosen as the best platform to be used. Interviews and questionnaires are the tools used to acquire the required input and to get user’s feedback towards the application developed. The paper will provide detailed discussion on the processes involve throughout the application development and the benefits that the application could provide to the user.